2019
DOI: 10.1108/aeat-01-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the unsteady aerodynamics of NACA 0012 with suction surface protrusion

Abstract: Purpose The purpose of this paper is to investigate the effect of surface protrusions on the flow unsteadiness of NACA 0012 at a Reynolds number of 100,000. Design/methodology/approach Effect of protrusions is investigated through numerical simulation of two-dimensional Navier–Stokes equations using a finite volume solver. Turbulent stresses are resolved through the transition Shear stress transport (four-equation) turbulence model. Findings The small protrusion located at 0.05c and 0.1c significantly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Meanwhile, for airfoil empennage, NACA 0009 was used as airfoil data obtained from the UIUU Catalog [8], [14]. This data is then revalidated with the help of XFRL5 software and comparison with relevant research [3], [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, for airfoil empennage, NACA 0009 was used as airfoil data obtained from the UIUU Catalog [8], [14]. This data is then revalidated with the help of XFRL5 software and comparison with relevant research [3], [16].…”
Section: Methodsmentioning
confidence: 99%
“…The cirrus sailplane is designed with two different airfoils. One of the examples of a cirrus sailplane is FX 66-27 ALL-182, designed by Dr. FX Wortmann at the University of Stuttgart [3]. Later, computer-aided software is employed to assist glider designs in improving performance [4].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that airfoil with a nose having a shorter length and medium depth shows a noticeable increase in aerodynamic efficiency almost at all angles of attack (Arif et al , 2019). It has also been reported that triangular protrusion at the leading edge can significantly enhance the lift produced by an airfoil (Bodavula et al , 2019). They also showed that at low Reynolds number the pre-stall aerodynamic characteristics of National Advisory Committee for Aeronautics (NACA) 0012 is greatly improved and the stall is mitigated with smaller protrusion near the leading edge (Bodavula et al , 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Although many researchers have attempted to use different types of indentations of different sizes, depths, and placement types, both above and below a surface, to summarize this, the depths of a single type of cavity can be tested on different regions of an airfoil surface. Numerical investigation done on the triangular cavity type by Bodavula A, helped gain valuable insights on the effect of adding either cavity and protrusions on the cavity on the airfoil body also helped choose a pre-existing design for the test airfoil [17,18,19]. Provided the research on the solver model done by the former, which employs transition Shear Stress Transport equations to stabilize the solution with the transport equations, this is deemed as an efficient method for getting accurate results in a fluid simulation [20,21].…”
Section: Introductionmentioning
confidence: 99%